The love of neighbour in ancient Judaism : the reception of Leviticus 19:18 in the Hebrew Bible, the Septuagint, the Book of Jubilees, the Dead Sea Scrolls, and the New Testament - Akiyama, Kengo, 1985- (Ancient Judaism and Early Christianity, 2018)
In The Love of Neighbour in Ancient Judaism , Kengo Akiyama traces the development of the mainstay of early Jewish and Christian ethics: \'Love your neighbour.\' Akiyama examines several Second Temple Jewish texts in great detail and demonstrates a diverse range of uses and applications that opposes a simplistic and evolutionary trajectory often associated with the development of the \'greatest commandment\' tradition. The monograph presents surprisingly complex interpretative developments in Second Temple Judaism uncovering just how early interpreters grappled with the questions of what it means to love and who should be considered as their neighbour.